More than consent for ethical open-label placebo research - Specker Sullivan, Laura (Journal of medical ethics, 2021)
Recent studies have explored the effectiveness of open-label placebos (OLPs) for a variety of conditions, including chronic pain, cancer-related fatigue and irritable bowel syndrome. OLPs are thought to sidestep traditional ethical worries about placebos because they do not involve deception: with an OLP, patients or subjects are told outright that they are not given an active substance. As deception is framed as the primary hurdle to ethical placebo use, the door is ostensibly opened to ethical studies of OLPs. In this article, I suggest that even though OLPs seemingly do not involve deception, there are other ethical considerations in their clinical investigation and subsequent use. Research ethics often focusses on informed consent—of which, deception and honesty are a piece—as a means to justify research practices with human subjects. Yet, it is but one of the ethical considerations that should be taken into account. With research into placebo effects in particular, I argue that the history of clinical placebo use grounds special considerations for OLP research that go beyond respect for the autonomy of individual patients through informed consent and encompass structural concerns about the type of patient for whom a placebo has historically been thought appropriate.There are no data in this work.